Edukasi Tentang Undang-Undang Perlindungan Konsumen di Era Digital dan Pasar Bebas (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
In the digital era and free market, technology is growing rapidly. Consumers and businesses are now more inclined to use digital transactions rather than face-to-face cash transactions. This study aims to find solutions and receive feedback related to the implementation of the Consumer Protection Law in the Digital Era and Free Market. The method used in this activity is through counseling and discussion. From the results of this activity, it was concluded that Law No. 8 of 1999 concerning Consumer Protection needs to be updated immediately as it is no longer relevant to the current digital technology, which has advanced far and is different from the conditions in 1999 when the consumer protection law was issued. The results of this activity indicate that the Consumer Protection Law No. 8 of 1999 requires comprehensive updates to accommodate the development of digital transactions, personal data protection, and consumer rights in cyberspace. Furthermore, the importance of educating consumers about their rights in digital transactions is also a key focus, so that the public can avoid losses resulting from unsafe online transactions.